β-Thalassemia Intermedia: Interaction of α-Globin Gene Triplication With β-thalassemia Heterozygous in Spain - Ropero, Paloma; González Fernández, Fernando Ataúlfo; Nieto, Jorge M.; Torres-Jiménez, Williana Melissa; Benavente, Celina (Frontiers in Medicine, 2022)
OBJECTIVES: To verify with hematimetric data that the diagnosis and clinical grade of β-TI can be established when a triplication of alpha genes (αααanti 3.7) and heterozygous β-thalassemia coexist. MATERIAL AND METHODS: Retrospective study in which 73 patients of Caucasian origin participated, who simultaneously showed a triplication or quadruplication of genes α and β-thalassemia. Screening for the most frequent α-thalassemia mutations as well as gene triplication (αααanti 3.7) was carried out by multiplex PCR followed by reverse hybridization with a commercial Alpha-Globin StripAssay kit and confirmed by MLPA. The molecular diagnosis of β-thalassemia was carried out by automatic sequencing according to the Sanger method. RESULTS: The genotypes have been classified into three groups according to the number of α globin genes and the severity of the alteration in the β globin gene. All had a mutation in the HBB gene (β0-thalassemia, β+-thalassemia severe, and β+-thalassemia mild). Group I patients who have coherent 6 α genes and groups II and III with 5 α globin genes. In group III, the patients were carriers of mutations affecting the β and δ globin genes. The most significant hematological parameters were hemoglobin levels, MCV, RDW, and the percentage of Hb F. CONCLUSIONS: In group I, regardless of the distribution of the 6 α globin genes, homozygous triplication (ααα/ααα) or heterozygous quadruplication (αααα/αα), the association with heterozygous β-thalassemia results in severe to moderate anemia that may or may not require transfusion therapy, is the severity of the HBB gene mutation that would determine the clinical variation. Group II patients phenotypically behaved like mild thalassemia intermedia, except for one case that presented thalassemic trait because it also presented an associated α-thalassemia (ααα/-α3.7). Finally, group III patients behaved as a thalassemic trait since all were carriers of mutations that increase the overexpression of γ genes.